Strategi Implementasi Smart Office Untuk Meningkatkan Efektivitas Pelayanan Publik Di Dinas Pendidikan Provinsi Sulawesi Selatan - Laode Imran; Mulyadi Hamid; St Rukaiyah (Jurnal Online Manajemen ELPEI, 2026)
The rapid development of digital technology has encouraged public institutions to reform bureaucratic work systems in order to improve effectiveness, transparency, and accountability. The South Sulawesi Provincial Education Office has implemented a Smart Office system as a digital administrative platform to support the improvement of public service quality. However, the implementation of digital systems does not always run optimally, as it is influenced by organizational readiness, human resource capacity, and the availability of supporting technological infrastructure. This study aims to analyze the strategy for implementing Smart Office and to identify the supporting and inhibiting factors affecting the effectiveness of public services. This research employs a qualitative approach, with data collected through open-ended interviews conducted via Google Forms and document analysis. A total of 22 informants were involved, including senior officials, structural officers, administrative staff, system operators, school principals, teachers, and education service users. The data were analyzed using thematic analysis based on 40 response variables and supported by policy documents related to Smart Office and the Electronic-Based Government System (SPBE). The findings indicate that Smart Office implementation contributes to faster administrative processes, improved document traceability, and increased transparency and accountability. Nevertheless, challenges remain in terms of technological infrastructure limitations, digital literacy gaps among employees, and the lack of systematic training and evaluation. Therefore, a sustainable and well-coordinated implementation strategy is required to ensure that digital transformation delivers tangible improvements in public service quality within the education sector.